Overexpression of microRNA-194 suppresses the epithelial–mesenchymal transition in targeting stem cell transcription factor Sox3 in endometrial carcinoma stem cells - Baolan Gong; Yan Yue; Renxiao Wang; Yi Zhang; Quanfang Jin; Xi Zhou (Tumor Biology)
The epithelial–mesenchymal transition is the key process driving cancer metastasis. MicroRNA-194 inhibits epithelial–mesenchymal transition in several cancers and its downregulation indicates a poor prognosis in human endometrial carcinoma. Self-renewal factor Sox3 induces epithelial–mesenchymal transition at gastrulation and is also involved epithelial–mesenchymal transition in several cancers. We intended to determine the roles of Sox3 in inducing epithelial–mesenchymal transition in endometrial cancer stem cells and the possible role of microRNA-194 in controlling Sox3 expression. Firstly, we found that Sox3 and microRNA-194 expressions were associated with the status of endometrial cancer stem cells in a panel of endometrial carcinoma tissue, the CD133+ cell was higher in tumorsphere than in differentiated cells, and overexpression of microRNA-194 would decrease CD133+ cell expression. Silencing of Sox3 in endometrial cancer stem cell upregulated the epithelial marker E-cadherin, downregulated the mesenchymal marker vimentin, and significantly reduced cell invasion in vitro; overexpression of Sox3 reversed these phenotypes. Furthermore, we discovered that the expression of Sox3 was suppressed by microRNA-194 through direct binding to the Sox3 3′-untranslated region. Ectopic expression of microRNA-194 in endometrial cancer stem cells induced a mesenchymal–epithelial transition by restoring E-cadherin expression, decreasing vimentin expression, and inhibiting cell invasion in vitro. Moreover, overexpression of microRNA-194 inhibited endometrial cancer stem cell invasion or metastasis in vivo by injection of adenovirus microRNA-194. These findings demonstrate the novel mechanism by which Sox3 contributes to endometrial cancer stem cell invasion and suggest that repression of Sox3 by microRNA-194 may have therapeutic potential to suppress endometrial carcinoma metastasis. The cancer stem cell marker, CD133, might be the surface marker of endometrial cancer stem cell.